Síntese, elucidação estrutural e estudos in silico de novos compostos 2-amino-tiofênicos imídicos candidatos a fármacos antifúngicos, antileishmanicida e antitumorais - Pereira, Ana Ligia da Costa (2019)
Cryptococcosis, leishmaniasis, and cervical adenocarcinoma are challenging diseases for medical chemistry. In order to bring new treatments for these diseases, the in silico studies (ADMET and molecular docking) and organic synthesis have been used to validate new molecular targets and to develop new drugs. Bearing in mind that 2-amino-thiophene and cyclic imides are shown as attractive pharmacophores for these 3 diseases, the aim of this work was to synthesize 2-amino-thiophene-imidic hybrids and perform in silico ADMET and molecular docking studies for new targets key molecules for growth and metabolism microorganisms Cryptococcus neoformans and leishmania and tumor cells like cervical adenocarcinoma, aiming the prediction of compounds potentially more active for these targets, for future conduction of biological tests. Firstly, several synthetic methodologies were tested, among which the solvent-free reaction method at 150ºC was chosen to obtain the different hybrid derivatives. Thiophene-imidic hybrids were synthesized with determined physicochemical characteristics and confirmed structures through 1H and 13C nuclear magnetic resonance spectroscopy, mass spectrometry and X-ray diffraction (for CNF08 and ESF-07). SwissADME and Osiris Property Explore software were used in the in silico ADMET studies, where it was observed that hybrids containing maleimides and phthalimides presented better bioavailability and gastrointestinal absorption profiles, with the CNMA-06 and ESMA-06 compounds showing the best value of drugscore. Most compounds have no potential for interaction with cytochrome CYP450 CYPCD6, CYPC3A4, or P-gp isoforms, especially bis-indolyl hybrids (for example ESDP-06 and IPDP-06). Only IPDP-06 and all bis-indolines may exhibit toxic effects. Molecular docking studies were conducted using Molegro Virtual docking 6.0 software, using 3 to 4 molecular targets for each disease. All molecules presented negative values of interaction energy, indicating great potential to bind with stability and affinity to the selected macromolecules. The best ligands for the targets were the isoindolinesic hybrids, especially bis-indolinic ones, which have -COOEt radical at the C-3 position of the thiophene nucleus. Relating the results in silico ADMET and molecular docking, it was observed that the compound ESFA-06 presented ideal profile for bioavailability and interaction with the macromolecules studied. In addition, bisimides, mainly IPBT-06, have a multi-target profile, for Cryptococcosis, Leishmania and cervical adenocarcinoma, which suggests a great therapeutic potential by stimulating the tests to confirm biological activities.